2004
DOI: 10.1021/jp037040k
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics Study of the N(4S) + O2 Reaction and Its Reverse

Abstract: We report quasiclassical trajectory calculations for the reaction N(4 S) + O 2 f NO + O by focusing on the rovibrational distributions of the NO product molecule at a collisional energy of 3 eV and the temperature dependence of the rate constant. The calculations employ the lowest adiabatic sheet of a recently reported (Varandas, A. J. C. J. Chem. Phys. 2003, 119, 2596) multisheeted double many-body expansion potential energy surface for the 2 A′ states of NO 2 , improved via a multiple energy-switching scheme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(74 citation statements)
references
References 50 publications
5
69
0
Order By: Relevance
“…They, respectively, are This last equation is the same reported in Ref. [40]. Details on the calculation of both the equations are reported in the Appendix A.…”
Section: Backward Rate Coefficientsmentioning
confidence: 93%
“…They, respectively, are This last equation is the same reported in Ref. [40]. Details on the calculation of both the equations are reported in the Appendix A.…”
Section: Backward Rate Coefficientsmentioning
confidence: 93%
“…Such three-body correction terms, which have been included by dressing the input diatomic curves, have been calibrated using both theoretical and experimental data. After diagonalization, a manifold of eight 2 A′ potential energy surfaces is obtained, with the lowest adiabatic state having been morphed with an effective spectroscopic polynomial form 25 26 The number of reported studies for the 1 2 A′′ electronic state is much smaller than that for the ground state. Gillespie et al 27 reported bending curves for the equilibrium NO distance of the NO 2 molecule, which have been used by Duff and Sharma 20 to construct a global potential energy surface.…”
Section: Potential Energy Surfacesmentioning
confidence: 99%
“…Reaction ͑1͒ has been the subject of a large number of experimental [17][18][19][20][21][22][23][24][25][26] and theoretical [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] investigations. The experimental studies have focused on two aspects: first, to evaluate thermal rate coefficients over a wide range of temperatures from 300 to 5000 K, 19,24,25 and second, to determine the rovibrational level populations of the NO͑͒ products.…”
Section: Introductionmentioning
confidence: 99%